2006
DOI: 10.1016/s0022-5347(06)00515-5
|View full text |Cite
|
Sign up to set email alerts
|

Altered Nitric Oxide Synthase, Arginase and Ornithine Decarboxylase Activities, and Polyamine Synthesis in Response to Ischemia of the Rabbit Detrusor

Abstract: Enzymes related to L-arginine catabolism were involved in the early events of ischemic bladder. Arginase may have 2 independent roles, that is 1) activation of arginase/ornithine decarboxylase/polyamines pathways in the muscle injury and remodeling following ischemia, and 2) endogenous negative regulation of nitric oxide production by limiting the L-arginine substrate for nitric oxide synthase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
0
14
1
2
Order By: Relevance
“…In the rat, intravesical administration of NO depressed bladder hyperactivity induced by chemical irritants (20)(21)(22)(23)(24)(25). After damage to the urinary bladder, NO generation is most likely caused by i-NOS, which in other tissues is up regulated by inflammatory stimuli and the activity of which is independent of calcium concentration (13).…”
Section: Discussionmentioning
confidence: 99%
“…In the rat, intravesical administration of NO depressed bladder hyperactivity induced by chemical irritants (20)(21)(22)(23)(24)(25). After damage to the urinary bladder, NO generation is most likely caused by i-NOS, which in other tissues is up regulated by inflammatory stimuli and the activity of which is independent of calcium concentration (13).…”
Section: Discussionmentioning
confidence: 99%
“…Arginase is a 105‐kD homotrimeric enzyme that requires manganese for the hydrolysis of L‐arginine to form L‐ornithine and urea. Because L‐arginine is the substrate of both arginase and NOS, arginase activity can effectively inhibit NO‐dependent processes by depleting the substrate pool available for NO biosynthesis, for example, as observed in the cellular immune response and the regulation of smooth muscle tone 41–43 . Accordingly, arginase inhibition can effectively enhance NO‐dependent physiological processes by enhancing L‐arginine bioavailability to NOS 44–47 .…”
Section: Modulation Mechanisms Of No (Fig 2)mentioning
confidence: 99%
“…Arginase also has an important role in providing l ‐ornithine for the synthesis of polyamines controlling cell proliferation and differentiation. Ornithine decarboxylase (ODC) is the rate limiting enzyme for the conversion of l ‐ornithine to putrescine, which is further converted to spermidine by spermidine synthase 8 …”
Section: Role Of Arginasementioning
confidence: 99%
“…Also, we reported that, in the early events of ischemic bladder, arginase may have two independent roles, that is (i) the activation of arginase/ODC/polyamine pathways in the muscle injury and remodeling following ischemia; and (ii) the endogenous negative regulation of NO production by limiting the l ‐arginine substrate for NOS 8 …”
Section: Role Of Arginasementioning
confidence: 99%
See 1 more Smart Citation